2 D Self‐Assembly and Catalytic Homo‐coupling of the Terminal Alkyne 1, 4‐Bis(3, 5‐diethynyl‐phenyl)butadiyne‐1, 3 on Ag(111). Issue 11 (12th August 2013) - Cirera, Borja; Zhang, Yi‐Qi; Klyatskaya, Svetlana; Ruben, Mario; Klappenberger, Florian; Barth, Johannes V.
Abstract The covalent linking of terminal alkynes is a promising approach for the bottom‐up fabrication of novel, carbon‐rich or all‐carbon materials, which was recently extended towards interfacial architectures. Here we report the synthesis of a novel organic species (1, 4‐bis(3, 5‐diethynylphenyl)butadiyne‐1, 3) and employ it to engineer self‐assembled supramolecular layers and covalent networks on the Ag(111) surface. Samples are prepared in‐situ under ultra‐high vacuum conditions and examined at the molecular level with scanning tunneling microscopy. After evaporating the two‐fold symmetric molecule onto the substrate at temperatures below 300 K and subsequent cooling to 5 K we find highly regular supramolecular phases commensurate with the underlying silver surface and stabilized mainly by weak, non‐covalent interactions originating from the terminal ethynyl moieties. Annealing at temperatures between 350 and 500 K triggers catalytic conversions with the pertaining covalent coupling reactions resulting in small aggregates or irregular polymeric networks. Our detailed analysis of the binding motifs demonstrates that two competing reaction pathways dominate the covalent linking processes. The first is the Glaser–Hay‐type homo‐coupling of two alkyne terminations leading to a linear butadiyne bridge. The second is the connection of a butadiyne group to a laterally attacking terminal alkyne, converting the attacked ethyne to ethene moieties, which presents a major obstacle for the production of regular networks.